Layered Social Network Analysis Reveals Complex Relationships in Kindergarteners - Golemiec, Mireille; Schneider, Jonathan; Boyce, W. Thomas; Bush, Nicole R.; Adler, Nancy; Levine, Joel D. (Frontiers in Psychology, 2016)
The interplay between individuals forms building blocks for social structure. Here, we examine the structure of behavioural interactions among kindergarten classroom with a hierarchy-neutral approach to examine all possible underlying patterns in the formation of layered networks of ‘reciprocal’ interactions. To understand how these layers are coordinated, we used a layered motif approach. Our dual layered motif analysis can therefore be thought of as the dynamics of smaller groups that tile to create the group structure, or alternatively they provide information on what the average child would do in a given local social environment. When we examine the regulated motifs in layered networks, we find that transitivity is at least partially involved in the formation of these layered network structures. We also found complex combinations of the expected reciprocal interactions. The mechanisms used to understand social networks of kindergarten children here are also applicable on a more general scale to any group of individuals where interactions and identities can be readily observed and scored.